Penerapan Peraturan Daerah Pada Sektor Kelautan Dan Perikanan di Provinsi Kepri - Rufinus H. Hutauruk; Ampuan Situmeang; Raja Taufik Zulfikar (Journal of Judicial Review, 2015)
The background of the study was about the problems in the policy and implementation of Riau Islands Province Regional Regulation Number 2 Year 2009 about the long-term plan in the effort to eliminate poverty in naval and fishery potential basis to increase the prosperity of Riau Islands Province people in coastal area specifically and Indonesians generally. The problems discussed in this study were about the obstacles in implementing the naval and fishery sector development and the solution to overcome the problems.The absence of basic infrastructure, the low education level, the geographical conditions of occupied islands all over Riau Islands Province area which were heavily influenced by the climate, and the lack of human resources to execute the programs made it slow to reach the targeted change in implementing the naval and fishery development policy.For the development continuation, it is recommended to Riau Islands Province Local Government along with Riau Islands Province People’s Regional Representative Council to issue a Local Regulation to make naval and fishery development to be the main priority in increasing the prosperity of the people as the maritime economy power basis in NKRI framework as the Foremost Islands Province, increasing the control, coordination, and synergy between sectors with related institute in formulating and implementing the naval and fishery development policy, reexamining the aid receivers, making an agreement with a clear regulation and binding the aid receivers.